Mitosis count and number of cancer cells in cases of primary pulmonary adenocarcinoma: Correlations among phosphorylated histone 3, number of cancer cells, nuclear grade, pathologic features and prognosis. Issue 3 (2nd February 2018) - Inoue, Takashi; Nakazato, Yoshimasa; Karube, Yoko; Maeda, Sumiko; Kobayashi, Satoru; Chida, Masayuki
Abstract : Immunohistochemistry findings for the phosphorylated form of histone 3 (pHH3) have been shown to be a reliable mitosis‐specific marker. We evaluated the correlation between pHH3‐stained mitotic figures (PHMFs) and clinical outcome, and compared the results with findings for numbers of PHMFs and cancer cells. The primary tumor was obtained from 113 patients with pulmonary adenocarcinomas (≤2 cm maximum dimension). All specimens were stained with pHH3, then the number of cancer cells in each was determined. Cases with a cancer‐cell index ≥1000 showed worse recurrence‐free survival as compared to those with a value <1000 ( P < 0.001). Also, cases with a pHH3 index ≥0.27 showed worse recurrence‐free survival as compared to <0.27 ( P = 0.001) and cases with a pHH3/cancer‐cell index ≥0.001 showed worse recurrence‐free survival as compared to <0.001 ( P = 0.002). Multivariate analysis demonstrated that pHH3/cancer‐cell index was significantly correlated with prognosis, but not Ki‐67 index. The number of cancer cells was also strongly correlated with progression of Noguchi's classification and WHO pathologic type. pHH3/cancer‐cell index was correlated with prognosis, and those were useful for prognostic evaluation of pulmonary adenocarcinoma patients. Furthermore, cancer cell number was correlated with Noguchi's classification and WHO pathologic type.